1990
DOI: 10.1002/jhrc.1240130709
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the SCD and FPD for HRGC determination of atmospheric sulfur gases

Abstract: SummaryThe FPD and the new SCD have been examined for their respective performance characteristics as sulfur selective detectors for HRGC in the determination of atmospheric sulfur gases. Overall, the SCD was an extremely selective and sensitive sulfur gas detector with lower MDLs than the FPD and fewer problems with interferences and noise stability, thus allowing the SCD more flexibility in capillary column selection. Modification of the FPD, however, provided more symmetrical peaks and greater resolution th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 15 publications
2
21
0
Order By: Relevance
“…Eq. (2)) Gaines et al, also reported [10] that there was only little effect of probe height on the SCD response. Although the probe height has little effect on the chromatographic efficiency, the hydrogen flow rate dictates the position of the probe in the flame housing and significantly affects the sensitivity of the flame SCD.…”
Section: Effect Of Probe Height Of Scd On the Efficiencymentioning
confidence: 84%
See 1 more Smart Citation
“…Eq. (2)) Gaines et al, also reported [10] that there was only little effect of probe height on the SCD response. Although the probe height has little effect on the chromatographic efficiency, the hydrogen flow rate dictates the position of the probe in the flame housing and significantly affects the sensitivity of the flame SCD.…”
Section: Effect Of Probe Height Of Scd On the Efficiencymentioning
confidence: 84%
“…The efficiency of thick-film capillary columns has been evaluated by Ettre [6], Sandra et al [7] and in the theoretical treatments of Ogan [8] and Leclercq et al [9]. Several authors published their results by using thick-film capillary gas chromatography coupled with a sulfur chemiluminescence detector (SCD) to analyze highly volatile sulfur compounds and great improvement in the separation and quantitative results have been achieved [10,11,12]. Band-broadening in capillary columns follows the Golay equation [13].…”
Section: Introductionmentioning
confidence: 99%
“…However, GC with SCD is an outstanding combination for selective detection of trace concentration of sulphur-containing compounds in different kinds of samples. The SCD possesses advantages over other sulphur selective detectors and it is finding widespread application in the analysis of petrochemical products [40 -42], natural gases [43], foods and beverages [44,45], environmental samples [46], perfume, fragrances etc. The SCD was first developed as an analyser for the determination of sulphur compounds in air [47], and later it was commercialised as a GC detector utilising an FID-style arrangement operated under hydrogen-rich conditions to generate sulphur monoxide (SO) as the basis of chemiluminescence [48].…”
Section: Sulphur Chemiluminescence Detector (Scd)mentioning
confidence: 99%
“…This GC system employed a J&W DB-Wax megabore column to obtain superambient temperature separations [Barinaga and Farwell, 1987;Gaines et al, 1990] of volatile sulfur gases. Under optimized laboratory conditions, this GC/SCD system achieved a detection limit of 3 pptv SO2 using a 2-min cryogenic preconcentration and a 50 sccm sample flow.…”
Section: Quality Control Equipmentmentioning
confidence: 99%